Les infections Respiratoires - BENHALOUIA, Nesrine (My University, 2021)
Respiratory bacterial infections are a publichealth problem because of their frequency and potential severity; they are a major cause of mortality in the world. objective of our study was estimated the prevalence of respiratory infections bacterial at the CHU MUSTAPHA (Algiers) and to identify the bacteria responsible for them and their susceptibility profiles to antibiotics. 71 patients had a respiratory infection, with a prevalence rate of 38.58%. Bacterial identification showed a predominance of HaemophilusSpp with (16.48%) for Gram negativebacilli and Staphylococcus Spp (7.69%) for Gram positive cocci. 22 isolated bacteria showed antibiotic multidrug resistance (24.17%) of the total isolated bacteria, thus , leading to therapeutic dead . The fight against respiratory infections must go through hygiene measures in the hospital, as well as a policy of antibiotic prescription adapted to the evolution of bacterial resistance.
Keywords: Bacterial respiratory infection, prevalence, multidrug resistance, Bacteria.